Drug-Induced Behavioral Changes: Using Laboratory Observations to Predict Field Observations - Klaminder, Jonatan; Hellström, Gustav; Fahlman, Johan; Jonsson, Micael; Fick, Jerker; Lagesson, Annelie; Bergman, Eva; Brodin, Tomas (Frontiers in Environmental Science, 2016)
Behavioral assays constitute important research tools when assessing how fish respond to environmental change. However, it is unclear how behavioral modifications recorded in laboratory assays are expressed in natural ecosystems, a limitation that makes it difficult to evaluate the predictive power of laboratory-based measurements. In this study, we hypothesized that exposure to a benzodiazepine (i.e., oxazepam) increases boldness and activity in laboratory assays as well as in field assays – that is, laboratory results can be used to predict field results. Moreover, we expected the modified behavior to affect other important ecological measures such as habitat selection and home range. To test our hypothesis, we exposed European perch (Perca fluviatilis) to oxazepam and measured subsequent changes in behavioral trials both in laboratory assays and in a lake ecosystem populated with a predatory fish species, pike (Esox lucius). In the lake, the positions of both perch and pike were tracked every three minutes for a month using acoustic telemetry. In the laboratory assay, the oxazepam-exposed perch were bolder and more active than the non-exposed perch. In the lake assay, the oxazepam-exposed perch were also more bold and active, had a larger home range, and used pelagic habitats more than the non-exposed perch. We conclude that ecotoxicological behavioral assays are useful for predicting the effects of exposure in natural systems. However, although individual responses to exposure were similar in both the laboratory and field trials, effects were more obvious in the field study, mainly due to reduced variability in the behavior measures from the lake. Hence, short-term behavioral assays may fail to detect all the effects expressed in natural environments. Nevertheless, our study clearly demonstrates that behavior modifications observed in laboratory settings can be used to predict how fish perform in aquatic ecosystems.